OPTIMASI PRODUKSI TUTUP BOTOL 500 ml PADA PROSES INJECTION MOULDING MENGGUNAKAN METODE RESPONSE SURFACE - Kurniawan Purnama Putra; R. Koekoeh R. W. (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Injection molding is one of the most common operations and versatile for mass production of complex plastic components. Injection molding is a process of plastic forming into a desired shape by means of pressing molten plastic into a space (cavity). Injection molding has a multi-step process, starting from inserting plastic pellets into the hopper, then plastic pellets into barrels / heating which makes the plastic material is melted. Melting plastic material is driven by the rotation of the screw, so that the flow to the nozzle, and then toward the sprue, runner, gate and into the cavity. Then the material present in the cavity will be retained within the mold under a certain pressure (holding pressure) to keep no shringkage when the product cooling process (cooling).The purpose of this study was to obtain the optimization of the cycle time and the percentage of production reject the bottle cap 500 ml in PT Berlina Tbk. The method used for this research is the method of response surface analysis, method surface respone is statistical and mathematical methods used to examine the relationship between one or more variables with the qualitative form of the response variables that aims to optimize and develop the response in an experiment. The data is optimized using Minitab software 16 produces an output response parameter setting optimization to inject pressure, nozzle temperature and cooling time. From the data analysis using the software Minitab 16 is obtained from the optimum situation results generated under conditions injection amounting to 1420 bar pressure; nozzle temperature at 264.7912 ° C; and the cooling time of 14.08 seconds. In this state of production can be increased by 10.836%. From the state of the optimum cycle time generated is 27.9161 seconds, net produced according to the standard that is 33.5820 grams and reject percentage the resulting is 11.11%. With a cycle time 27.9161 seconds with a net according to the standard and the percentage of rejects decreased 3.89%, the resulting product amounts to ± 15,517 /shift or up approximately 10.836%. The amount is based on the number of products produced in the cycle time previous of 30 seconds to produce ± 14,000 /shift. Keywords: Injection moulding, box-benhken design, Response surface methodology